Evaluating the Suitability of the Simplified Pairs Trading Strategy for Short-term Equity Market Trading - Mosina, Julija; Žilinskij, Grigorij (Comparative Economic Research. Central and Eastern Europe, 2025)
Pairs trading has been a successful tool for traders since its inception in the 1980s and has evolved significantly with the introduction of algorithmic, machine, and AI trading. This evolution has complicated the implementation of this strategy that traditionally benefits institutional or specialized investors. Despite this, the simplicity of pairs trading remains accessible, indicating potential benefits for ordinary traders. By focusing on the strategy’s fundamental principles and employing a real-time market test on a popular trading platform, the study aims to reveal its applicability and efficacy for short-term equity trading. Utilizing basic trading platform tools and Excel functions, the research aims to demonstrate a simplified approach to pairs trading. The findings will provide insights into the strategy’s effectiveness, providing non-expert traders with a viable approach to navigate today’s volatile markets through a simplified yet effective pairs trading model. The experiment’s findings highlight varying performances across different stock pairs, with notable differences in volatility. While five out of 11 pairs achieved positive returns, only two met the closure criteria within the short-term horizon, suggesting that a longer trading period and a more diversified pair’s portfolio may be necessary to fully capture expected price convergence.